Observations of unexpected grain boundary migration in SrTiO3. (1st January 2023) - Muralikrishnan, Vivekanand; Liu, He; Yang, Lin; Conry, Bryan; Marvel, Christopher J.; Harmer, Martin P.; Rohrer, Gregory S.; Tonks, Michael R.; Suter, Robert M.; Krill, Carl E.; Krause, Amanda R.
Abstract: High-energy x-ray diffraction microscopy (HEDM) nondestructively maps microstructures in 3D, allowing for the same grains and boundaries to be tracked over time during annealing experiments. Here, HEDM was applied to observe grain growth in strontium titanate. These results are compared to a 3D isotropic grain growth simulation that starts from the same initial microstructure to identify potentially unknown grain boundary migration mechanisms. During the simulation, grain growth behaves as expected: the change in grain volume is correlated with the number of neighbors, and the grain boundary velocity is correlated with its local curvature. Experimentally, however, flat boundaries were found to move faster than curved boundaries, and 37% of all measured boundaries move in the direction opposite to their curvature. These unexpected observations suggest that, in materials with anisotropic grain boundary properties, mechanisms other than curvature-driven boundary migration play a role in the minimization of interfacial energy. Graphical abstract: Image, graphical abstract